And the wolf finally came : the decline of the American steel industry - Hoerr, John P., 1930- (Pittsburgh series in social and labor history., 1988)
A veteran reporter on American labor, John P. Hoerr analyzes the spectacular and tragic collapse of the steel industry in the 1980s. And the Wolf Finally Came demonstrates how an obsolete and adversarial relationship between management and labor made it impossible for the industry to adapt to a rapidly changing global economy.